Concurrent EGFR Mutation and ALK Translocation in Non-Small Cell Lung Cancer - Sweis, Randy F (Cureus, 2016)
Epidermal growth factor receptor (EGFR) mutations and anaplastic large-cell lymphoma kinase (ALK) rearrangements are now routine biomarkers that have been incorporated into the practice of managing non-small cell lung cancer (NSCLC). Historically, the two molecular alterations have been viewed as mutually exclusive, but recent identified cases suggest otherwise. In this report, we describe cases of lung cancer with concurrent EGFR mutation and ALK rearrangement and identify their clinical characteristics. Non-small cell lung cancer patients with multiple molecular alterations were retrospectively analyzed from an academic referral center from 2011–2013. An additional review was conducted of reported cases with dual alterations. Four cases of NSCLC with alterations in both EGFR and ALK were identified and evaluated with 16 published cases for a total of 20 cases. The age of patients ranged from 37 to 77 years. Nine patients were never smokers. The disease control rates in patients treated with EGFR inhibitors and ALK inhibitors were 46% (6/13) and 71% (5/7), respectively. This series highlights the importance of comprehensive molecular profiling of newly diagnosed lung cancer, as NSCLC may be driven by concurrent molecular alterations. EGFR- and ALK-targeted therapies appear to have modest activity in patients with tumors possessing both alterations. Dual-altered NSCLC patients may have distinct clinical characteristics warranting further study. Combination targeted therapy or novel multi-targeted tyrosine kinase inhibitors may prove important in these patients, though necessary studies remain ongoing.